NATO and the Environment: The Committee on the Challenges of Modern Society. (5th April 2016) - RISSO, LINDA
Abstract: Launched with considerable fanfare in 1969, the Committee on the Challenges of Modern Society (CCMS) was supposed to bring new life to NATO by both re-energising public support and engaging with a variety of themes, issues and partners well beyond the alliance's traditional scope. The first aim of this article is to go beyond the careful media operation that surrounded the launch of the CCMS and to examine the scepticism and resistance of some European partners, particularly the British. The second aim is to demonstrate that NATO started to think in terms of crisis management, disaster relief and environmental disasters well before 1989. The sheer military strength of the alliance and of its partners did remain central – and notably came back to the forefront in 1979 – but the alliance did start to see itself as a geopolitical player and to consider engagement beyond its strictly defined geographical area as early as 1969.